Characteristics of Communities Affected by Covid-19 on Archaeological Sites and Cultural Heritage Sites in Kalijambe, Sragen, Central Java in 2020 - Kuswaji Dwi Priyono; Ongky Fernanda (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the characteristics of the community affected by the Covid-19 Pandemic Outbreak on Archaeological Sites and Cultural Heritage Sites in KalijambE District, Sragen Regency, Central Java. The survey method was used in this study, with structured interviews with 78 respondents and 14 businessmen and traders in the tourism object. Determination of respondents using the Convenience Sampling method provided that the business owner is 1,000 m away from the museum with a circular pattern. The results of this study found that the socio-economic characteristics of the people affected by the Covid-19 pandemic experienced a decline in people's income with an average income of 3 million. The education level of the community around the museum is the highest in SMA and SMP. The number of family dependents is 1-3 people and the number of dependents of school age children is 1-2 people in one family head. The domination of the age group of the community around the museum is 25 - 45 years, the community is classified as productive. Factors that influence the development of the museum, namely, the economic factor of the community feels an increase in income with the existence of the museum. The social factor of the opening of wide employment opportunities makes the unemployment rate decrease so that the people around the museum live an easy life, fulfill their needs and reduce the level of employment.